2015
DOI: 10.1159/000369710
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticancer Potential of Dichloroacetate and Estradiol Analogue Exerting their Effect via ROS-JNK-Bcl-2-Mediated Signalling Pathways

Abstract: Background: C9, a newly in silico-designed inhibitor of microtubule dynamics induces G2/M arrest culminating in apoptosis. Dichloroacetate (DCA) inhibits pyruvate dehydrogenase kinase, an enzyme that promotes pyruvate entry into mitochondria. The use of antitumor drugs targeting different cancer features can be a more effective way to overcome drug resistance. Methods: The influence of C9 (130 nM) + DCA (7.5 mM) on MCF-7 and MCF-12 cells was assessed via microscopy spectrophotometry global gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 79 publications
2
21
0
Order By: Relevance
“…Accumulating evidence indicates that intracellular ROS can induce apoptosis and autophagy in cancer cells [34-37]. Thus, we examined the role of ROS generation in salidroside induced apoptosis and autophagy in SW1353 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence indicates that intracellular ROS can induce apoptosis and autophagy in cancer cells [34-37]. Thus, we examined the role of ROS generation in salidroside induced apoptosis and autophagy in SW1353 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated that the phosphorylation of JNK triggered by ROS induces phosphorylation of Bcl-2 [28]. Thus, activation of JNK signaling in cancer cells facilitates mitochondrial apoptosis by causing loss-of-function of Bcl-2 [29].…”
Section: Discussionmentioning
confidence: 97%
“…Activation of JNK induces phosphorylation of Bcl-2, thus suppressing the anti-apoptotic function of Bcl-2 [28]. As shown in Fig.…”
Section: Combination Of Cisplatin and Anti-mir-20a Induced Mitochondrmentioning
confidence: 90%
“…β-Elemene reversed chemoresistance by reducing resistance transmission via exosomes [43], and Cinnamaldehyde Derivative (CB-PIC) sensitized resistant cancer cells to drug-induced apoptosis via inhibition of STAT3 and AKT signaling [44]. Combination of two chemotherapeutics C9 and Dichloroacetate (DCA) showed synergistic effects in breast cancer cells through ROS-JNK-Bcl-2 pathways [45]. Recently, ABT-263, a BH3 mimetic, has been demonstrated to inhibit Aurora kinase inhibitor-induced polyploidy and produces a synergistic loss of viability in a range of cancer cell lines when combination with Aurora B inhibitors [30, 36].…”
Section: Discussionmentioning
confidence: 99%